A Survey on Tra Vinh University English Department Teachers' and English-Majored Students' Attitudes and Views on the Textbook - Interactions 2 Listening / Speaking - Silver Edition - Bui, Thi My Chi (Trường Đại học Mở; Tp. Hồ Chí Minh, 2024)
This study attempts to conduct a Survey of Tra Vinh University English Department teachers‟ and English-majored students‟ attitudes and views on the use of the Interactions 2 - Silver Edition by Tanka and Baker (2007a) published by McGraw-Hill, related to two skills: Listening and Speaking.